(untitled) (Web of Teachers: Inderscience Research, 2025)
This article attempts to analyze the work of the modern Russian writer Roman Senchin. Literary critics attribute the writer’s artistic work to the new literary trend «new realism». The following works of the author were analyzed: the short story «New Realism», «African Nights», the novel «Ice underfoot», the novel «Information». In these works, R. Senchin managed to put into practice the aesthetic requirements that the author himself imposed on the literature of new realism.